Pioneers of Adsorption Science 2. Sidney John Gregg - Kenneth S. W. Sing (Adsorption Science & Technology, 2015)
A short account is given of the life and work of Dr. S. John Gregg (1902–1999). Gregg's first research paper on the physical adsorption of gases appeared in 1927 and his last review of the subject was published in 1986. His extensive research contributions to adsorption science and surface chemistry should be remembered along with the generous guidance and encouragement he gave to three generations of academic and industrial scientists.